Nanostructured N/S doped carbon dots/mesoporous silica nanoparticles and PVA composite hydrogel fabrication for anti-microbial and anti-biofilm application - Pisut Pongchaikul; Tasnim Hajidariyor; Navarat Khetlai; Yu-Sheng Yu; Pariyapat Arjfuk; Pongtanawat Khemthong; Wanwitoo Wanmolee; Pattaraporn Posoknistakul; Navadol Laosiripojana; Kevin C.-W. Wu; Chularat Sakdaronnarong (Elsevier, 2023)
Regarding the convergence of the worldwide epidemic, the appearance of bacterial infection has occasioned in a melodramatic upsurge in bacterial pathogens with confrontation against one or numerous antibiotics. The implementation of engineered nanostructured particles as a delivery vehicle for antimicrobial agent is one promising approach that could theoretically battle the setbacks mentioned. Among all nanoparticles, silica nanoparticles have been found to provide functional features that are advantageous for combatting bacterial contagion. Apart from that, carbon dots, a zero-dimension nanomaterial, have recently exhibited their photo-responsive property to generate reactive oxygen species facilitating to enhance microorganism suppression and inactivation ability. In this study, potentials of core/shell mesoporous silica nanostructures (MSN) in conjugation with carbon dots (CDs) toward antimicrobial activity against Staphylococcus aureus, Pseudomonas aeruginosa and Escherichia coli have been investigated. Nitrogen and sulfur doped CDs (NS/CDs) conjugated with MSN which were cost effective nanoparticles exhibited much superior antimicrobial activity for 4 times as much as silver nanoparticles against all bacteria tested. Among all nanoparticles tested, 0.40 M NS/CDs@MSN showed the greatest minimal biofilm inhibitory at very low concentration (< 0.125 mg mL−1), followed by 0.20 M NS/CDs@MSN (0.5 mg mL−1), CD@MSN (25 mg mL−1), and MSN (50 mg mL−1), respectively. Immobilization of NS/CDs@MSN in polyvinyl alcohol (PVA) hydrogel was performed and its effect on antimicrobial activity, biofilm controlling efficiency, and cytotoxicity toward fibroblast (NIH/3 T3 and L-929) cells was additionally studied for further biomedical applications. The results demonstrated that 0.40 M NS/CDs-MSN@PVA hydrogel exhibited the highest inhibitory effect on S. aureus > P. aeruginosa > E. coli. In addition, MTT assay revealed some degree of toxicity of 0.40 M NS/CDs-MSN@PVA hydrogel against L-929 cells by a slight reduction of cell viability from 100% to 81.6% when incubated in the extract from 0.40 M NS/CDs-MSN@PVA hydrogel, while no toxicity of the same hydrogel extract was detected toward NIH/3 T3 cells.